REGIONAL FEATURES OF FOREIGN INVESTMENT ON THE EXAMPLE OF THE VOLYN REGION (Economic journal of Lesya Ukrainka Volyn National University, 2018)
In the article, the author analyzes the dynamics of the main indicators of foreign direct investments in the economy of the Volyn region during 2000–2016 on the basis of statistical data, and determines its main trends. The geographical and industrial structure of foreign direct investments is analyzed, the main investing countries and the main areas of investment are identified. The analysis of attraction of volumes of foreign investments into the economy of the region by towns and districts of the Volyn region is carried out. A list of key tasks aimed to stimulate the attraction of foreign investment in the economy of the Volyn region is proposed.
Keywords: investments, foreign direct investment, investment activity, region, Volyn region, investment attractiveness, foreign capital